Maroon Communities in South Carolina : A Documentary Record - Lockley, Timothy James, 1971- (Book collections on Project MUSE., 2009)
Maroon communities were small, secret encampments formed by runaway slaves, typically in isolated and defensible sections of wilderness. The phenomenon began as runaway slaves, unable to escape to safe havens in sympathetic colonies, opted instead to band together for survival near the sites of their former enslavement. In this first survey of documentary records of marronage in colonial and antebellum South Carolina, Lockley offers opportunity to assess the unique features and trends of the maroon experience in the Palmetto State. Lockley surveys eighteenth- and early-nineteenth-century historical sources gathered from newspaper reports, court proceedings, government and military records, correspondence, and reward advertisements to illustrate the efforts of white South Carolinians to locate maroon communities, defend against raiding parties, and kill or capture runaways living in these societies. -- from publisher marketing.